Current-voltage characterization and 3D device modelling of p-type induced junction photodiode; surface recombination velocity and bulk lifetime - Tang, Chi Kwong; Nordsveen, Marit Ulset; Gran, Jarle (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
A p-type silicon-based induced junction photodiode has been investigated with current-voltage (I-V) measurement under laser illumination at multiple power levels, and the results are fitted using 3D device simulations. When considering multiple laser power levels, it is found that material parameters that limit the performance of the photodiode can be extracted through fitting of a small voltage region of the I-V measurement.